Plastic Waste Management: Trasition to a Circular Economy - Md Ali, Umi Fazara; Za’aba, Siti Khadijah; Mohamed Sultan, Al Amin; Ahmad, Khairul Anuar (Lembaga Jurutera Malaysia, 2021)
The linear approach to manufacturing, use, and disposal in today's world economies is not sustainable financially or environmentally. A solution is the circular economy, which minimizes waste and reuses what is needed. Malaysia has started addressing plastic pollution by adopting a circular economy approach, eliminating unnecessary plastic production and focusing on alternative materials and circular design. This has led to a significant increase in the recovery and recycling of plastic waste, with the National Recycling Rate currently at 30.67%, a 2.61% increase from 2019. By 2025, the Ministry of Housing and Local Government aims to achieve a 40% National Recycling Rate.